The Impact of Quarrying on Aquatic Flora within the Middle Course of Sirwan River, Iraqi Kurdistan Region - Salar, Sarkawt Ghazi; Khalil, Mohammed I.; Othman, Arsalan A.; Ali, Salahalddin S.; Ahmad, Bakhtyar A.; Obaid, Ahmed K. (Revista de Ciências Agroveterinárias, 2025)
The Sirwan River, a tributary of the Tigris River, flows from the northwest of Iran and continues through the Iraqi Kurdistan region. It has undergone significant changes due to human activities over the past three decades. This research examines the geomorphological and biological changes from 1990 to 2022 caused by man-made disruptions. Fieldwork was conducted to determine and assess the occurrence of aquatic plants in ponds formed by quarrying along the middle course of the river, along with measurements of the ponds' chemical and physical properties. Satellite imagery from Landsat 5, Landsat 7, and Landsat 8 was used to analyze land cover changes over the study period. The images indicated substantial impacts of quarrying on land cover, with an increase in barren land at the expense of vegetation cover. According to the results, throughout 33 years, the vegetation cover declined and was replaced by bare soil. There was a clear, strong correlation between the two land cover classes: vegetation cover vs. barren soil (r=0.983, p < 0.05). Also, the results revealed significant changes in aquatic plant diversity between pond habitats and running water. We are recommending that monitoring of weed species distribution in the Sirwan River helps to mitigate ecological imbalances and protect both living and non-living river components. Additional research is required to identify strategies for minimizing the environmental impact of quarries in this region.